NILAI PENDIDIKAN KARAKTER DALAM TEKS BHAGAWAN DHOMYA: Seni Pendidikan Kuno untuk Sepanjang Masa - ni wayan purnamiasih (Jurnal PASUPATI, 2019)
Preservation of the legacy of literary works in the form of text is one of the efforts to preserve Indonesian culture to remain steady and maintain the noble values contained in it. The text of Bhagawan Dhomya in the book Ādi Parwa is a prose-shaped literary work with many values of character education as proclaimed by the government. Therefore, this research aims to determine the value of character education contained in the text of Bhagawan Dhomya. This research is a type of qualitative research with data analysis using descriptive - qualitative which includes data reduction, data presentation and conclusion drawing. The method of collecting data uses library research and documentation. The presentation technique of the results of data analysis in this study is to use a description that is clear and directed. From the results of the research, there are 18 values of character education contained in the text of Bhagawan Dhomya which is an ancient educational art but still relevant throughout the period, including: religious character, honesty, tolerance, discipline, hard work, creative, independent, democratic, curiosity the spirit of nationalism, love of the country, respect for achievement, friendship, peace of mind, love to read, care for the environment, caring for the social and the character of responsibility.